Desain Model Monate: Movie Analysis and Debate untuk Pembelajaran Literasi Sosial - Utami, Fariza Wahyu; Wardani, Li’anatus Sukma; Segara, Nuansa Bayu (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
Literacy skills in the 21st century for the cognitive development of any student are vital. Various literacy skills are a derivative of 21st-century skills. Social literacy is one of the goals of the social studies learning process. It is also necessary to improving supporting abilities such as the ability to communicate, collaborate and think critically for each student. They can mount their competencies through learning experiences from the surrounding environment. One of the innovations is for improving students' social literacy skills in social studies learning is using the "MONATE" (Movie Analysis and Debate) learning model. The "MONATE" learning model uses films as a form of material delivery as innovative learning. The method used in developing this Learning Model is ADDIE (analysis, design, develop, implement, evaluate). In this article, we only discuss the progress stage of the development of this MONATE Model. The analysis stage is out by conducting a literature study related to social studies learning competencies. The design stage is a process to design a learning model that is by the learning objectives. The development stage is out by validating the social studies learning model developer experts for a desk appraise. The result is that there are several model developments, especially in the learning syntax and learning media used. The improvement of this model becomes the basis for conducting further research processes.